Unraveling the interplay between norovirus infection, gut microbiota, and novel antiviral approaches: a comprehensive review - Bai, Geng-Hao; Tsai, Meng-Chen; Lin, Sheng-Chieh; Hsu, Yi-Hsiang; Chen, Shih-Yen (Frontiers in Microbiology, 2023)
Norovirus infection is a leading cause of acute gastroenteritis worldwide and can also cause harmful chronic infections in individuals with weakened immune systems. The role of the gut microbiota in the interactions between the host and noroviruses has been extensively studied. While most past studies were conducted in vitro or focused on murine noroviruses, recent research has expanded to human noroviruses using in vivo or ex vivo human intestinal enteroids culture studies. The gut microbiota has been observed to have both promoting and inhibiting effects on human noroviruses. Understanding the interaction between noroviruses and the gut microbiota or probiotics is crucial for studying the pathogenesis of norovirus infection and its potential implications, including probiotics and vaccines for infection control. Recently, several clinical trials of probiotics and norovirus vaccines have also been published. Therefore, in this review, we discuss the current understanding and recent updates on the interactions between noroviruses and gut microbiota, including the impact of norovirus on the microbiota profile, pro-viral and antiviral effects of microbiota on norovirus infection, the use of probiotics for treating norovirus infections, and human norovirus vaccine development.